Analysis of the Chinese Natural Gas Power Generation Cost under the Market Linkage Mechanism. (May 2017) - Jiang, Shumin; Zhen, Zaili; Tian, Lixin; Lou, Liyun
Abstract: The excessive carbon emissions caused by the fossil energy has caused people's attention. Many large-scale power generation project adopt the substitution natural gas for original thermal power generation. This paper use the real option theory to evaluate the cost of nature gas power generation and original thermal power generation. Particularly, the linkage of domestic and international markets is regarded for the natural gas price. The costs of existing thermal power generation and natural gas power generation are simulations in random paths. Results show that the cost of natural gas power generation is less than the cost of existing thermal power generation as a whole. What's more, there are obvious difference in the natural gas power generation cost with and without the market linkage. The market linkage of nature gas price is helpful to steady the fluctuation of natural gas price and decrease the investment risk. Thus, in the perspective of power generation enterprise, the natural gas power generation under market linkage could save the cost of power generation enterprise in long period.